Platinum-Catalyzed α,β-Unsaturated Carbene Formation in the Formal Syntheses of Frondosin B and Liphagal - Huynh, Khoi Q. (Org Lett, 2016)
Formal syntheses of tetracyclic terpenoids frondosin B and liphagal are described. Both synthetic routes rely on the use of platinum-catalyzed α,β-unsaturated carbene formation for the key C–C bond forming transformations. The successful route toward frondosin B utilizes a formal (4 + 3) cycloaddition, while the liphagal synthesis features the vinylogous addition of an enol nucleophile as a key step. Both synthetic routes are discussed, revealing insights into structural requirements in the catalytic α,β-unsaturated carbene reaction manifold.